Microbial metabolites indole derivatives sensitize mice to D-GalN/LPS induced-acute liver failure via the Tlr2/NF-κB pathway - Zhou, Ziyuan; Wang, Baohong; Pan, Xiaxia; Lv, Jiawen; Lou, Zhuoqi; Han, Yuqiu; Yao, Yuanyuan; Chen, Jun; Wang, Qiangqiang; Li, Lanjuan (Frontiers in Microbiology, 2023)
Acute liver failure (ALF) is a clinical condition with many causes, fast progression, and a poor prognosis. Previous research has indicated that microbial factors have a role in ALF, but a clear picture has yet to emerge. To investigate the specific involvement of microbial metabolites in ALF development, we pretreated D-GalN/LPS-induced ALF mice with indole derivatives, an influential class of gut microbial metabolites. Contrary to their typical role as anti-inflammatory agents in the host, indole-3-acetic acid (IAA), indole-3-lactic acid (ILA), and indolepropionic acid (IPA) gavage sensitize mice to D-GalN/LPS-induced-ALF with a rapid rise in serum transaminases and histologic lesion. For a clearer picture, we performed comprehensive analysis for the IAA therapy. IAA markedly amplified inflammatory response and cellular damage. The transcriptome analysis indicated the participation of the TNF-α/ NF-κB signaling pathway. The structure of gut microbiota in ileum and the expression of TOLL-like receptor 2 (Tlr2) in the liver were also significantly changed. In conclusion, IAA pretreatment can exacerbate D-GalN/LPS-induced ALF via probable Tlr2/ NF-κB pathway involvement and ileac dysbiosis. Microbial metabolites IAA may aggravate individual susceptibility to D-GalN/LPS-induced ALF. Further investigation of the underlying mechanism is needed, and intervention with indole derivatives and related commensal species should be undertaken with caution.